Comparison of Biomarkers to Differentiate Chronic Kidney Disease and Chronic Kidney Disease of Unknown Etiology: Life Sciences-Biochemistry - Rajyalakshmi, Nakka; Rajagopalan, Vijayaraghavan; Sivanesan, Senthilkumar; Sabhavatu, Vijaya (International Journal of Life Science and Pharma Research, 2022)
Chronic kidney disease of unknown etiology (CKDU) is prevalent and clinically silent until its late stages at which patient may suffer significant irreversible damage, or mortality in the absence of early screening and intervention. CKDU is asymptomatic but may show nonspecific symptoms. Conventional markers are influenced by multiple non-renal factors while Kidney injury molecule-1(KIM-1) and Neutrophil gelatinase-associated lipocalin(NGAL) are promising biomarkers of chronic kidney disease (CKD), there are no studies reported so far on these markers in CKDU. The aim of the study is to assess the sensitivity of biomarkers serum KIM-1 and NGAL in patients with CKDU in comparison with CKD and controls. To achieve this, our objectives are to estimate the level of biochemical parameters like serum creatinine, urea, uric acid, random blood sugar, systolic and diastolic blood pressure and hemoglobin and to compare novel biomarkers KIM-1 and NGAL in CKDU patients with CKD. The serum levels of urea, uric acid, creatinine, KIM-1 and NGAL were estimated in control, CKD and CKDU (n = 35, 46, 79 respectively). Creatinine showed 8.1-fold and 2.7-fold increase (P <0.001), and urea 4.0% and 1.8% increase (P < 0.001), compared to control in CKD and CKDU cohorts, respectively. The sensitivity and specificity of KIM-1 was 73.4% and 67.4%with a cutoff value of 203.5ng/mL using the receiver operating characteristic(ROC) curve. For NGAL they were 82.3%, 73.9% and 255ng/mL. Compared to control, KIM-1 showed a 51.5-fold and 87.2-fold increase in CKD and CKDU, respectively (P < 0.001). NGAL showed a 4.8-fold and 6.7-fold increase in CKD and CKDU, respectively (P < 0.001). Creatinine and urea were higher in CKD than in CKDU, whereas KIM-1 and NGAL were higher in CKDU than CKD. KIM-1 and NGAL are sensitive biomarkers for CKDU. KIM-1 can differentiate CKD and CKDU.